Identification and Characterization of Three Epithiospecifier Protein Isoforms in Brassica oleracea - Witzel, Katja; Abu Risha, Marua; Albers, Philip; Börnke, Frederik; Hanschen, Franziska S. (Frontiers in Plant Science, 2019)
Glucosinolates present in Brassicaceae play a major role in herbivory defense. Upon tissue disruption, glucosinolates come into contact with myrosinase, which initiates their breakdown to biologically active compounds. Among these, the formation of epithionitriles is triggered by the presence of epithiospecifier protein (ESP) and a terminal double bond in the glucosinolate side chain. One ESP gene is characterized in the model plant Arabidopsis thaliana (AtESP; At1g54040.2). However, Brassica species underwent genome triplication since their divergence from the Arabidopsis lineage. This indicates the presence of multiple ESP isoforms in Brassica crops that are currently poorly characterized. We identified three B. oleracea ESPs, specifically BoESP1 (LOC106296341), BoESP2 (LOC106306810), and BoESP3 (LOC106325105) based on in silico genome analysis. Transcript and protein abundance were assessed in shoots and roots of four B. oleracea vegetables, namely broccoli, kohlrabi, white, and red cabbage, because these genotypes showed a differential pattern for the formation of glucosinolate hydrolysis products as well for their ESP activity. BoESP1 and BoESP2 were expressed mainly in shoots, while BoESP3 was abundant in roots. Biochemical characterization of heterologous expressed BoESP isoforms revealed different substrate specificities towards seven glucosinolates: all isoforms showed epithiospecifier activity on alkenyl glucosinolates, but not on non-alkenyl glucosinolates. The pH-value differently affected BoESP activity: while BoESP1 and BoESP2 activities were optimal at pH 6-7, BoESP3 activity remained relatively stable from pH 4 to 7. In order test their potential for the in vivo modification of glucosinolate breakdown, the three isoforms were expressed in A. thaliana Hi-0, which lacks AtESP expression, and analyzed for the effect on their respective hydrolysis products. The BoESPs altered the hydrolysis of allyl glucosinolate in the A. thaliana transformants to release 1-cyano-2,3-epithiopropane and reduced formation of the corresponding 3-butenenitrile and allyl isothiocyanate. Plants expressing BoESP2 showed the highest percentage of released epithionitriles. Given these results, we propose a model for isoform-specific roles of B. oleracea ESPs in glucosinolate breakdown.